O impacto da implementação do código florestal na mitigação dos efeitos das mudanças climáticas na flora do Cerrado - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The Cerrado biome is home to a large number of endemic species. However, despite its importance, Cerrado suffers a significant habitat loss due to ecosystems being affected by anthropic actions, such as replacing natural areas and climate change. The combination of climate change and the reduction of natural areas causes a decrease in biological diversity and local extinctions of plants. The Cerrado is one of the biomes most affected by the loss of natural areas. Here we evaluate how the distribution of endemic and threatened flora species of the Cerrado will be affected by climate change and how changes in land use in different scenarios of forest code implementation will contribute to mitigating the consequences of climate change. We developed species richness maps for three emission scenarios, an optimistic (SSP126), an intermediate (SSP245), and a pessimistic (SSP585) scenario projected to the year 2050 for 242 endemic and threatened Cerrado species. In addition, we analyzed the change in species distribution incorporating the different land use scenarios relative to the implementation of the forest code, baseline scenarios - deforestation control, and FC - full forest code implementation. The baseline scenario considers that control of illegal deforestation is imperfect or partial, and the FC scenario considers full forest code implementation, with restoration of deforested areas and allowing only legal deforestation. The different land use scenarios will lead to less distribution loss; partial and full forest code implementation could improve species protection and conservation. Most species (239) will have their distribution reduced in the best scenarios (optimistic emission scenario and with full implementation of the forest code). There will be no change in only three species, while eight species will become extinct, with 76 species losing more than 75% of their suitable area, in the FC scenario with SSP585. However, if only the climatic scenario is taken into account, there will be a reduction in distribution, and 53 species could lose >75% of the suitable area in the SSP585 emission scenario. The southern and southeastern regions of the Brazilian Cerrado will be the areas with future climatic suitability for most species. Consequently, the conservation of species, which are endemic and already classified as threatened in the Cerrado, will be further affected.
Keywords: Savana; Mudanças climáticas; Distribuição das espécies - Modelos; Uso da terra; Código Florestal Brasileir; Savanna; Climate change; Species distribution - Models; Land use change; Brazilian Forest Code; CIENCIAS BIOLOGICAS; OUTROS